A Novel Method for Evaluating the Combustion Characteristics of Carbon Materials and Mold Fluxes. Issue 3 (25th November 2020) - Gu, Shaopeng; Yu, Liang; Wen, Guanghua; Tang, Ping; Wang, Zhe; Jiang, Wenbo
Abstract : The combustion characteristic of mold fluxes is extremely important for the high‐quality slabs and the smooth casting process, which is directly determined by the type and content of carbon materials. Herein, the physicochemical properties and combustion characteristics of carbon materials are investigated by field emission scanning electron microscopy, X‐ray diffraction, Brunauer–Emmett–Teller theory, and thermogravimetry (TG) and differential scanning calorimetry (DSC), followed by the influences of carbon materials on the combustion and melting behavior of mold fluxes. The results show that: 1) the fixed carbon content in single‐carbon materials and carbon‐added mold fluxes can be determined by TG curves; 2) the combustion temperature ranges and the combustion reaction time of single‐carbon materials and carbon‐added mold fluxes can be characterized by DSC curves; and 3) the combustion characteristics of carbon are influenced by mold fluxes, leading to a shorter combustion reaction time. The reduction of combustion reaction time for 1# and 2# being 7.5 and 8.2 min is much larger than that of 2.4 min for 3#. Finally, the melting behavior of mold fluxes is influenced by carbon, especially the melting temperature, flowing temperature, and the melting time, showing an increase trend. However, the softening temperature shows little change. Abstract : A novel method is proposed to research the combustion characteristics of different carbon materials added to mold fluxes, and then, the effect of different carbon materials on the combustion and melting behavior of mold fluxes is analyzed. The results show that the novel method can well characterize the combustion properties of carbon materials and be easily operated.